«Invisible lasting trace» by Yermek Serkebayev (Journal of Philosophy Culture and Political Science, 2018)
This article gives a brief overview of the life and work of Yermek Serkebayev as a great Kazakh singer, a teacher who is an example of imitation for creative youth.Key words: musical execute, lyrical baritone, partner of the great singers, king of baritones.